Hermeneutika Al Quran Tafsir Al-Azhar (Analisi Hermeneutis Ayat-ayat Akidah dan Ibadah) - pathur rahman (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2018)
Hamka's interpretation of al-Azhar in his interpretation clearly reveals the operational-functional hermeneutics of the Qur'an, although methodologically it is not as a whole and synergistic in representing the Qur'an's hermeneutics as a method of interpretation.